Jicotea en Estados Unidos: Lydia Cabrera y el puente antropomórfico a la diáspora cubana. - Fernández, Carlos Velazco (Hispanic Review)
The corpus of writer Lydia Cabrera (Havana, 1899–Miami, 1991) has been approached from various angles, particularly with a focus on one of her recurring protagonists, Jicotea. Inspired by the Trachemys decussata , a small turtle native to Cuba, Jicotea's shifting identity—moral and physical—has been the subject of literary analyses, religious interpretations, and studies in gender and queer perspectives. However, I argue that following Cabrera's departure from Cuba in 1960, Jicotea serves as an anthropomorphic link that articulates the recontextualization of Afro-Cuban religions in the North American diasporic space. After delving into her published short stories, essays, and private correspondence, I suggest that Cabrera, through shaping Jicotea as a symbol representing the historical reality of Cuban exile, engages with an ecological ethic rooted in the African-inspired religiosity of the Cuban diasporic communities in the United States.